Analysis of Students’ Motivation in Carrier-Based English Language Learning - Sundari, Misana Tri (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This study analyzes the impact of Carrier-Based Learning (CBL) on students' motivation and language proficiency in English language learning. Grounded in Self-Determination Theory (SDT) and the concept of situated learning, CBL integrates career-relevant tasks into the learning process to enhance intrinsic motivation and practical language skills. The research examines how CBL fosters autonomy, competence, and relatedness among students, leading to increased engagement and deeper learning. A comprehensive literature review methodology was employed to synthesize findings from various studies, highlighting the benefits and challenges of implementing CBL. Results indicate that CBL significantly improves students' motivation and language proficiency by providing authentic, meaningful learning experiences. However, successful implementation requires adequate teacher training and innovative assessment methods. This study underscores the importance of aligning language education with real-world career demands to prepare students for future professional success. The findings offer valuable insights for educators and policymakers on effectively integrating CBL into language curricula, promoting both academic and professional growth.